1984
DOI: 10.33584/jnzg.1984.45.1657
|View full text |Cite
|
Sign up to set email alerts
|

Management of Late Spring-Early Summer Pasture Surpluses in Hill Country

Abstract: Comparisons of controlling late spring to early summer pasture growth on either easy or steep contoured land with either a fast rotation or continuous grazing policy were made in self-contained farmlets for two years. Pasture control was maintained over more land by controlling steep land first and with continuous grazing. Animal performances (ewes, steers) were generally similar for the mid-November to early January treatment period, and subsequently until May shearing. In the first year better animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Management of late spring surpluses to restrict reproductive growth will increase summer pasture quality through a reduction in accumulated stem and dead material and encourage the proliferation of clover that will increase pasture quality later in the season (Sheath et al 1987). This can be achieved using severe and frequent defoliation through hard continuous grazing (Clark et al 1982;Korte et al 1984) or high frequency (short rotation) rotational grazing (Sheath et al 1984). A greater degree of pasture control on steepland may be achieved with continuous grazing, although, compared to rotationally grazed drought conditions or in summer-dry climates (Sheath et al 1984).…”
Section: Practicesmentioning
confidence: 99%
“…Management of late spring surpluses to restrict reproductive growth will increase summer pasture quality through a reduction in accumulated stem and dead material and encourage the proliferation of clover that will increase pasture quality later in the season (Sheath et al 1987). This can be achieved using severe and frequent defoliation through hard continuous grazing (Clark et al 1982;Korte et al 1984) or high frequency (short rotation) rotational grazing (Sheath et al 1984). A greater degree of pasture control on steepland may be achieved with continuous grazing, although, compared to rotationally grazed drought conditions or in summer-dry climates (Sheath et al 1984).…”
Section: Practicesmentioning
confidence: 99%
“…Pasture surpluses are often a problem on New Zealand hill country during thesummer, especially on steeper slopeswhich are lesspreferred than low slopes by sheep (Sheath 1981). Sheath et al (1983) recommends thecontrolof steeper areas by grazing management with deferred control of low slope areas.…”
Section: Ryegrass Browntop and Other Grasses Classmentioning
confidence: 99%
“…The appropriateness of the regression equation coefficients can partially be established by comparing the values with experimental results and field observations. For example, Fitzharris & Wright (1984) showed that increased subdivision was associated with higher farm productivity, whereas Sheath et al (1984) have demonstrated that control of late spring -early summer pasture production, such as that which can be obtained by increasing stocking rate through retiring areas for lamb feed, will improve subsequent animal and pasture performance.…”
Section: D7mentioning
confidence: 99%